Undergraduate Student’s Readiness Toward The Adoption of Study Technology for Learning in Kwara State, Nigeria - Amos Ochayi Onojah; I O Abimbola; O O Obielodan; Charles O OLumorin; Adenike Janet Aderogba; Christianah Adeyanju (IJER (Indonesian Journal of Educational Research), 2019)
Study technology is the technology of learning it all, knowing it all, using it all and recalling it all. In this study, the researcher examined the undergraduate students’ readiness toward the adoption of study technology for learning. The research adopted a cross-sectional studies descriptive research of the survey type. The sample comprised of four hundred and fifty undergraduate students. A structured questionnaire was utilized in collecting data while percentage and mean were used to answer the research questions, independent t-test was used to analysed the data collected. The results of the study revealed that undergraduate students are ready to adopt study technology for learning. There was no significant difference between male and female undergraduate students readiness towards the adoption of study technology for learning. Recommendation were however made that learning environments in schools should be equipped to enhance the readiness of undergraduate students to learn effectively and that the federal and state ministries of education should make appropriate plans to increase the extent of readiness for both male and female students to adopt study technology learning style in their studies